Peculiarities of Pre-Competitive Psychological Factors, Sport Performance Indicators and Physiological Demands in Youth Golf - Marius Zienius; Antanas Skarbalius; Aurelijus Kazys Zuoza; Kazimieras Pukėnas (Baltic journal of sport & health sciences, 2018)
Background. Sport performance indicators, physiological demands and psychological hallmarks are the key factors in the development of golf performance. However, no research was found in youth golf. We hypothesized that the peculiarities of pre-competitive psychological factors, sport performance indicators, physiological demands in youth golf are not adequate compared with adult golf. Methods.  Ten male golfers participated in this study. The aim of the research was to assess and evaluate the peculiarities of pre-competitive psychological factors, sport performance indicators, physiological demands in youth golf. Sport performance indicators in golf were recorded using a personal sport performance statistical protocol. Locomotion and physiological demands were recorded using the FRWD W 400  Series (Finland) device. Competitive state anxiety was assessed with the Competitive State Anxiety Inventory-2 (CSAI-2). The CSAI-2 assesses two components of state anxiety, cognitive and somatic anxiety, as well as a related construct, self-confidence. Results.  The subjects’ long-game skills were at a higher level than their short-game skills. Pre-competitive cognitive and somatic anxiety was low, but self-confidence was high. Training effect on young golfers’ aerobic fitness was low (1.28 – recovery zone). Conclusions. Opposite to elite golfers, the long-game skills of youth golfers are more developed than their short-game skills. Playing golf does not have a positive training effect on young golfers’ aerobic fitness. High level of self-confidence in youth golfers, which is adequate to elite golfers, could be determined by the similar level of  mastership among competitive participants. Keywords: cognitive and somatic anxiety, self-confidence, long-game skills, short-game skills, aerobic fitness.